Acute, hepatitis-A super-infection in HBV carriers, or chronic liver disease related to HBV or HCV - C. Pramoolsinsap (2018)
The impact of acute super-infection with hepatitis A virus (HAV) was determined in 20 asymptomatic carriers of the surface antigen (HBsAg) of hepatitis B virus (HBV), eight patients with HBV-related chronic liver discase (CLD), and four patients with CLD related to hepatitis C virus (HCV). For comparison, 100 patients with isolated HAV infection were also studied. The HBsAg carriers and patients with CLD related to HBV or HCV were significantly older than the patients with isolated HAV infection, with mean (S.D.) ages of 43.9 (14.1), 46.4 (16.0), 52.5 (8.6) and 28.4 (10.7) years, respectively (P ≤ 0.02). There were no significant between-group differences in the baseline serum concentrations of alanine aminotransferase. All the patients with isolated HAV infection fully recovered. Fulminant or submassive hepatitis occurred in 11 (55%) of the HBsAg carriers and four (33%) of the 12 patients with CLD related to either HBV or HCV. Nine of the 15 patients with severe hepatitis died and the mortality rate among the HBsAg carriers was not significantly different from that among the CLD patients (25% v. 33%; P = 0.15). These fatal cases were all aged > 50 years and were significantly older [59.0 (2.1) years] than the six severe cases who recovered [43.2 (10.7) years] as well as the remaining 17 uncomplicated cases with CLD or HBsAg [40.3 (13.0) years] (P ≤ 0.001). The results indicate that acute HAV is rarely fatal in young adults but may be severe and potentially fatal in patients with underlying chronic HBV or HCV infection, especially among the elderly. Vaccination against HAV should be considered for the patients at high risk who are negative for anti-HAV.